MENINGKATKAN HASIL BELAJAR BOLA VOLI DENGAN PENDEKATAN PERMAINAN LIBAS PADA SISWA KELAS IV SD NEGERI KARANGANYAR 01 TAHUN AJARAN 2013/ 2014 (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2015)
The purpose of this study is to determine the improvement of learning outcomes volleyball game approach libas on Elementary School fourth grade students Karanganyar 01 Sub Karanganyar Demak academic year 2013/2014. Data collection techniques in this study using observation, documentation, and a check list. The data analysis technique used is descriptive qualitative data. Results showed before applying the initial data libas game only 8 students with a percentage of 28.6 % . After the game libas applied in learning volleyball at the first cycle the number of students who completed as many as 21 students with a percentage of 75 %, so there is an increase from baseline of 46.4 %. In the second cycle the number of students who completed as many as 25 students with a percentage of 89.3 %, and an increase from the first cycle of 14.3 %. The conclusions of this research is to approach the game libas can improve learning outcomes volleyball in fourth grade student Karanganyar State 01.